Efek Imunomodulator Ekstrak Etanol Spons Melophlus sarasinorum Terhadap Aktivitas Fagositosis Sel Makrofag Pada Mencit Jantan Balb/C: Immunomodulatory Effects of Ethanol Extract of Melophlus sarasinorum Sponge Against Phagocytosis Activity of Macrophage Cells on Balb/C Male Mice - Wahyuni, Wahyuni; Yusuf, Muhammad Ilyas; Malik, Fadhliyah; Lubis, Adryan Fristiohady; Indalifiany, Astrid; Sahidin, I (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Immunomodulator is an ingredient or drug that can modulate immune system functions and activities. This study was conducted to determine the effect of ethanol extract of Melophlus sarasinorum sponge on macrophage phagocytosis activity. Twenty four male mice balb/c were divided into six groups. The first group received 100 mg/kg of ethanol extract of Melophlus Sarasinorum sponge, the second group received 200 mg/kg of ethanol extract of Melophlus sarasinorum sponge, the third group received 300 mg/kg of ethanol extract of Melophlus Sarasinorum sponge and the fourth group received 400 mg/kg of ethanol extract of Melophlus Sarasinorum sponge. The positive control group received Phyllanthus niruri linn extract (StimunoÂ®) 0,13 mg/g and the negative control group received NaCMC 0,5%. The extract was orally administered from first day to seventh day. On the eighth day, each of the mice was injected Staphylococcus aureus bacteria (SA) 0.5 mL intraperitoneally. Macrophage cell activity is calculated from smears of peritoneal fluid of mice. Increased doses of ethanol extract of Melophlus sarasinorum sponge increase the amount of macrophage phagocytosis activity that are 25,25% (negative control), 61,5% (positive control), 55,75% (100 mg/kg), 60,75% (200 mg/kg), 62,25% (300 mg/kg) dan 66,25% (400 mg/kg). The results showed that the ethanol extract of Melophlus sarasinorum sponge has the potential as immunomodulator at a doses of 300 mg/kgBB and 400 mg/kg with no significantly different effectiveness with positive control in increasing macrophage cell phagocytosis activity based on the result of post-hoc statistical test of Tukey (sig.> 0,05).